DEVELOPMENT OF CREATIVE COMPETENCE OF STUDENTS AS AN IMPORTANT ISSUE (Scientific journal of the Fergana State University, 2023)
Development of students' creative competence is an urgent task of today's education system. The purpose of the article is to explain the essence of this task. Research methods are conducted in a theoretical comparative method. Through the results of the research, the methods of developing creative competences are studied.